If it's not what You are looking for type in the equation solver your own equation and let us solve it.
(4x+27)/2=(x+1)/3
We move all terms to the left:
(4x+27)/2-((x+1)/3)=0
We calculate fractions
4x/()+(-((x+1)*2)/()=0
We calculate terms in parentheses: +(-((x+1)*2)/(), so:We get rid of parentheses
-((x+1)*2)/(
We multiply all the terms by the denominator
-((x+1)*2)
We calculate terms in parentheses: -((x+1)*2), so:We get rid of parentheses
(x+1)*2
We multiply parentheses
2x+2
Back to the equation:
-(2x+2)
-2x-2
Back to the equation:
+(-2x-2)
4x/()-2x-2=0
We multiply all the terms by the denominator
4x-2x*()-2*()=0
We add all the numbers together, and all the variables
4x-2x*()=0
| 17,950=100+50w | | (x-2)/(-4)+2=5 | | 16/10000=n/3500 | | 1/10000=n/3500 | | 2(x+4)-1=5(x+2) | | 2(x+4)-1=2(x+11) | | 1/1000=x/3500 | | 3(x-1)+4=2(x+11) | | 29-3x=-9x | | 2(x-5)+1=25 | | 4x-3-x=3x-7 | | 2y-2=4y+3 | | 2-(3x+1)-(-x+4)=x+6 | | 41x+20=102 | | (8a+4)=(a-4) | | 3/7y-5=1 | | -20a=0 | | 8x^2+4x=4x(2x-0) | | X^3-4x=20-5x | | 4x(-)12=28 | | 2x-15+3(x-1)-10x=20-3x+4(x-1) | | 8−4x=x+13 | | 3x/17=3/2 | | 7x+23=163 | | 2(5x-2)=10x-21 | | 2(2x+1)-2(x+3)=-15 | | 7x-3x=64 | | 8/6=a/10 | | x*0.02=70 | | -7=7.75(3+10k)-5k | | t^2+20t-96=0 | | x/4(x+4)-1=39 |